2023
DOI: 10.4168/aair.2023.15.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Spontaneous Urticaria in Hong Kong: Clinical Characteristics, Real-World Practice and Implications for COVID-19 Vaccination

Abstract: Purpose The real-world management and clinical characteristics of chronic spontaneous urticaria (CSU) in Hong Kong and its implications for coronavirus disease 2019 (COVID-19) vaccination are unknown. We investigated the clinical characteristics of patients with CSU and the role of an immunologist-led Urticaria Clinic as well as the impact of CSU on COVID-19 vaccine uptake in Hong Kong. Methods Longitudinal clinical data of 257 CSU patients were collected and analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
9
0
4
Order By: Relevance
“…For example patients with chronic inducible or chronic spontaneous urticaria (CSU) or asthma may develop urticaria/angioedema or wheeze during acute infections when oral non-steroidal anti-inflammatory drugs are administered together with different antibiotic classes and the infection acts as a co-factor ( 24 ). Up to 10% patients with CSU carry drug “allergy” labels, which often impede future medical treatments or therapies ( 25 ). Similarly, patients with mast cell activation syndromes may develop immediate hypersensitivity type reactions related to neuromuscular blocking agents rather than antibiotics administered during the perioperative period ( 26 ).…”
Section: Drug Reactions With Similar Stereotypical Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example patients with chronic inducible or chronic spontaneous urticaria (CSU) or asthma may develop urticaria/angioedema or wheeze during acute infections when oral non-steroidal anti-inflammatory drugs are administered together with different antibiotic classes and the infection acts as a co-factor ( 24 ). Up to 10% patients with CSU carry drug “allergy” labels, which often impede future medical treatments or therapies ( 25 ). Similarly, patients with mast cell activation syndromes may develop immediate hypersensitivity type reactions related to neuromuscular blocking agents rather than antibiotics administered during the perioperative period ( 26 ).…”
Section: Drug Reactions With Similar Stereotypical Reactionsmentioning
confidence: 99%
“…In individuals with multiple antibiotic allergy, one needs to consider if these patients truly have MDHS, MDIS, or whether a common unifying underlying chronic disorder may need to be excluded. For example patients with chronic inducible or chronic spontaneous urticaria (CSU) or asthma may develop urticaria/ angioedema or wheeze during acute infections when oral nonsteroidal anti-inflammatory drugs are administered together with different antibiotic classes and the infection acts as a co-factor (24). Up to 10% patients with CSU carry drug "allergy" labels, which often impede future medical treatments or therapies (25).…”
Section: Drug Reactions With Similar Stereotypical Reactionsmentioning
confidence: 99%
“…In the current issue of Allergy, Asthma & Immunology Research , Kan et al 12 evaluated real-world CU management in Hong Kong and emphasized the role of immunologists/allergists in effectively treating CU and avoiding inappropriate COVID-19 vaccine hesitancy. A substantial proportion of CU patients in Hong Kong received inappropriate treatments, including regular first-generation H1-antihistamines and systemic corticosteroids, and had persistently uncontrolled disease.…”
mentioning
confidence: 99%
“…Although there is no evidence of the increased frequency of severe allergic reactions to the COVID-19 vaccine in CU patients, and CU is not a contraindication for COVID-19 vaccination, 14 there are concerns regarding COVID-19 vaccination in CU patients. Kan et al 12 found that a significantly lower proportion of CU patients received 2 doses of the COVID-19 vaccine than the general adult population (65% vs. 73.2%, respectively). Notably, previous studies have not found increased allergic responses to vaccines in CU patients.…”
mentioning
confidence: 99%
“…Despite genuine vaccine or excipient allergy being exceedingly rare, the indirect consequences from the fear of potential excipient allergy and inability to identify potential excipients among culprit drug formulations greatly impeded vaccine uptake and fuelled vaccine hesistancy. [16][17][18] To overcome these issues, the Comprehensive Excipient and Drug Allergy Registry (CEDAR) was established in Hong Kong -allowing the use of big data to investigate reported drug allergies in detail, and to help establish an excipient registry to facilitate comprehensive drug allergy evaluations. Utilising CEDAR, we investigated the 5-year trend of detailed drug allergy epidemiology and the potential role of an excipient registry to aid drug allergy evaluation.…”
mentioning
confidence: 99%